Modeling the dynamics of contractual relations - Griffo, Cristine; Araujo, Lauro César; Meira Brasil, Samuel; Marques, Mamede-Lima; Guizzardi, Giancarlo; Almeida, João Paulo A. (Frontiers in Artificial Intelligence, 2023)
Contracts usually have clauses that enable contracted parties to adjust their contractual positions in time, e.g., to relieve another party from a duty or to grant a new permission. This is especially important in long-running service relations, which require contracts to be adjusted to accommodate new or unforeseen circumstances. Despite that, the representation of dynamic aspects of contractual relations have not been given enough attention in the literature. In this paper, we address this gap by employing the notions of legal power and legal subjection. We propose an ontological analysis of unilateral contractual changes based on a well-founded legal core ontology that adopts a relational perspective for legal positions. We present a case study to show the benefits of representing the different types of contractual changes and how these changes can impact contractual dynamics. The case study is based on recent changes to WhatsApp terms of service.